Da tradição ao mercado: construção social e caprinovinocultura no semi-árido - Gonçalves Junior, Oswaldo (2010)
The present study aims at understanding both the social construction of markets concerning sheep and goat raising in the Brazilian states of Rio Grande do Norte, Paraíba e Ceará and the relationship between this construction process and topics such as poverty and development. This case-study research is based on three current experiences in Mossoró (RN), Cabaceiras (PB) e Tejuçuoca (CE). The sheep and goat raising has its origin with the arrival of the Portuguese settlers in the 16th century. The traditional raising procedures and genetic problems that affected most part of these animals caused loss of productivity and profitability. It is also important to mention that the raising of those animals was judged as an inferior activity when compared to the cattle raising, the last enterprise was historically and socially associated with a privileged status. In practical terms, however, this is a preconception once sheep and goats are suitable for the kind of climate in the region (semi-arid). Besides, a culture of resistance has influence over the sheep and goats raising economical potential, and it is confronted with an ‘enthusiasts network’ comprised of key players associated with social institutions. Taking into consideration favorable market aspects, these actors are faithful to the cause of transmission of appropriate raising techniques to small family farmers in order to improve their life conditions. Apart from them, the federal government through a program to support financially the purchase of food (Programa de Aquisição de Alimentos) and milk (Programa do Leite), established public polices and partnership with some states in order to create a market to the products produced by the family farms and food safety to the beneficiaries of Fome Zero (program to eliminate hunger). This stimulated process brought a new productive arrangement that combined regional vocation, innovation and productive social inclusion of poor people. Furthermore, it is understood that the construction of socially oriented markets promotes the restablishment of social ties and bonds and amplifies the number of relationships with which the individuals had contact before living these practices.